Alligatorweed flea beetle Agasicles hygrophila Selman and Vogt (Coleoptera: Chrysomelidae: Halticinae) - Ted D. Center; James P. Cuda; Michael J. Grodowitz (EDIS, 2009)
EENY462, a 4-page illustrated fact sheet by Ted D. Center, James P. Cuda, and Michael J. Grodowitz, is part of the Featured Creatures collection. It describes this beetle that was the first insect ever studied for biological control of an aquatic weed — distribution, description, life cycle and biology, host, and economic importance. Includes references. Published by the UF Department of Entomology and Nematology, October 2009.